PENERAPAN COOKING CLASS BERBASIS ETNOPEDAGOGI MINANGKABAU UNTUK MENINGKATKAN PENGETAHUAN GIZI ANAK USIA DINI - Sandra Sonita; Sri Yunimar Ningsih; Nanik Setiawati; Fitria Sari (STKIP Subang, 2026)
Nutritional knowledge needs to be developed from an early age because it forms the foundation for children to develop healthy eating habits and a healthy lifestyle. However, in reality, early childhood knowledge about healthy and nutritious food is still low. Children tend to be unable to recognize types of nutritious foods and the importance of consuming healthy foods in everyday life. This study aims to improve nutritional knowledge of children aged 5–6 years through the implementation of cooking classes based on Minangkabau culinary ethnopedagogy. The type of research used is Classroom Action Research (CAR) with a qualitative approach. The study was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects were children aged 5–6 years. Data collection techniques were carried out through observation, interviews, and documentation with an indicator of success if the child's nutritional knowledge reaches an average score of 75% or the category of Developing According to Expectations (BSH). The results of the study indicate that the implementation of cooking classes based on Minangkabau culinary ethnopedagogy can improve nutritional knowledge of children aged 5–6 years. This improvement was carried out through the following steps: the teacher explained the cooking class activities, introduced traditional Minangkabau food tools and ingredients, introduced the nutritional content of food, guided children in simple cooking activities, provided an understanding of the importance of healthy and nutritious food, and conducted a question and answer session about the children's experiences after the activity. In addition to improving nutritional knowledge, the cooking class activities also helped introduce Minangkabau culinary culture and develop children's motor, social, language, and independence skills. The success of the study was marked by achieving an average score of at least 89%.